Paradiplomacy of West Nusa Tenggara Province in Achieving Net-Zero Emission - Rustam, Ismah; Subarkah, Alwafi Ridho; Karjaya, Lalu Puttrawandi (Intermestic: Journal of International Studies, 2024)
This study aims to determine the role of the sub-state in International Relations, namely West Nusa Tenggara (West Nusa Tenggara, NTB), which participated in the United Nations Climate Change Conference (COP-26) in Glasgow to reduce carbon emissions or achieve Net Zero Emission (NZE). This research used a conceptual approach that is para-diplomacy and environmental diplomacy. This analysis used a qualitative research method with five stages: data collection, data reduction, data presentation in the form of narratives, graphs, and tables, and the final stage is writing conclusions. This study indicates that sub-states can carry out diplomacy in overcoming global climate problems, West Nusa Tenggara which participated in the United Nations Climate Change Conference (COP-26) in Glasgow, was able to have its charm with several countries such as England, Sweden, Denmark, and the United States because NTB is seen to have the potential to develop renewable energy; moreover, it already has Provincial Regulation concerning the General Plan of Regional Energy to achieve the Net Zero Emission and it is in line with the objectives of the COP-26.